Ω-3 fatty acid supplement use in the 45 and Up Study Cohort. Issue 4 (11th April 2013) - Adams, Jon; Sibbritt, David; Lui, Chi-Wai; Broom, Alex; Wardle, Jonathan
Abstract : Objective: There has been a dramatic increase in the use of dietary supplements in Western societies over the past decades. Our understanding of the prevalence of Ω-3 fatty acid supplement consumption is of significance for future nutrition planning, health promotion and care delivery. However, we know little about Ω-3 fatty acid supplement consumption or users. This paper, drawing upon the largest dataset with regard to Ω-3 fatty acid supplement use (n=266 848), examines the use and users of this supplement among a large sample of older Australians living in New South Wales. Design: A cross-sectional study. Data were analysed from the 45 and Up Study, the largest study of healthy ageing ever undertaken in the Southern Hemisphere. Setting: New South Wales, Australia. Participants: 266 848 participants of the 45 and Up Study. Primary and secondary outcome measures: Participants' use of Ω-3, demographics (geographical location, marital status, education level, income and level of healthcare insurance) and health status (quality of life, history of smoking and alcohol consumption, health conditions) were measured. Results: Of the 266 848 participants, 32.6% reported having taken Ω-3 in the 4 weeks prior to the survey. Use of Ω-3 fatty acid supplements was higher among men, non-smokers, non-to-mild (alcoholic) drinkers, residing in a major city, having higher income and private health insurance. Osteoarthritis, osteoporosis, high cholesterol and anxiety and/or depression were positively associated with  Ω-3 fatty acid supplement use, while cancer and high blood pressure were negatively associated with use of Ω-3 fatty acid supplements. Conclusions: This study, analysing data from the 45 and Up Study cohort, suggests that a considerable proportion of older Australians consume Ω-3 fatty acid supplements. There is a need for primary healthcare practitioners to enquire with patients about this supplement use and for work to ensure provision of good-quality information for patients and providers with regard to Ω-3 fatty acid products.